Implementation of electronic dictionary based on medicinal plants of the Sabu community increases learning motivation of XII students at Mehara - Ngginak, James; Ledo, Mellissa E.; Ballo, Aprlliana; Karmin, Monika; Ame, Joni; Ngede, Alfandy; Ndun, Yersi M.; Bertolomeous Hano; Mibels Jon Heke (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Learning outcomes are an important part of achieving the learning process. Classroom learning must achieve learning objectives. To realize these objectives and learning outcomes, teachers need to plan and design learning as well as possible so that indicators of success can be realized. One thing that supports this is the use of learning media. Learning media is a medium that can convey learning messages and can be accepted and understood by students. In relation to this research, the researcher aims to conduct research by implementing a dictionary based on local plants in the Sabu area. The research method used is descriptive qualitative with a one-group pretest-posttest design. The number of students in the experimental class was 32. Based on the results of the study, a 2-tailed sig value (0.001) <0.05 was obtained, which means there was a significant difference in student learning motivation before and after the experimental treatment. Student learning motivation after the experiment was higher than student motivation before the experiment. Therefore, it can be said that the application of the illustrated dictionary has a significant effect on student learning motivation.